Surgical Treatment of Middle Cerebral Artery Aneurysms: Hints and Precautions for Young Cerebrovascular Surgeons - Sturiale, Carmelo Lucio; Rapisarda, Alessandro; Marchese, Enrico; Puca, Alfredo; Olivi, Alessandro; Albanese, Alessio (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Background and Objective Clipping is still considered the treatment of choice for middle cerebral artery (MCA) aneurysms due to their angioarchitectural characteristics as they are often bifurcation dysplasias, needing a complex reconstruction rather than a simple exclusion. Thus, maintaining this surgical expertise is of paramount importance to train of young cerebrovascular surgeons. To balance for the increasingly limited experience due the worldwide general inclination toward the endovascular approaches, it is important to provide to the young neurosurgeons rules and operative nuances to guide this complex surgery. We describe the technical algorithm we use to teach our residents to approach ruptured and unruptured MCA aneurysms, which may help to develop a procedural memory useful to perform an effective and safe surgery.Materials and Methods We reviewed our last 10 years' institutional experience of about 400 cases of ruptured and unruptured MCA aneurysms clipping, analyzing our technical refinements and the difficulties in residents and young neurosurgeons teaching, to establish fundamental key-points and design a didactic algorithm that includes operative instructions and safety rules.Results We recognized seven pragmatic technical key points regarding craniotomy, sylvian fissure opening, basal cisternostomy, proximal vessel control, lenticulostriate arteries preservation, aneurysm neck microdissection, and clipping to use as a didactic algorithm for teaching residents, and as operative instructions for inexperienced neurosurgeons.Conclusion In the setting of clipping MCA aneurysms, respect for surgical rules is of paramount importance to perform an effective and safe procedure, ensure the best aneurysm exclusion, and preserve the flow in collaterals and perforators.
Keywords: middle cerebral artery aneurysm; MCA aneurysms; minipterional approach; clipping; proximal control; vascular neurosurgery; residents' education.